Phosphaturic mesenchymal tumor-induced bilateral osteomalacia femoral neck fractures: a case report - Zhang, Yifan; Hu, Mingwei; Guo, Cuicui; Yang, Xue; Xiang, Shuai; Xu, Hao (Frontiers in Endocrinology, 2024)
Phosphaturic mesenchymal tumors (PMT) are rare and distinctive tumors that typically result in paraneoplastic syndrome known as tumor-induced osteomalacia (TIO). We report a case of bilateral osteoporotic femoral neck fracture caused by PMT. PMT was surgically resected, followed by sequential treatment of bilateral femoral neck fractures with total hip arthroplasty (THA). A 49-yearold perimenopausal woman experienced consistent bone pain with limb weakness persisting for over 2 years. Initially, she was diagnosed with early osteonecrosis of the femoral head and received nonsurgical treatment. However, from 2020 to 2022, her pain extended to the bilateral shoulders and knees with increased intensity. She had no positive family history or any other genetic diseases, and her menstrual cycles were regular. Physical examination revealed tenderness at the midpoints of the bilateral groin and restricted bilateral hip range of motion, with grade 3/5 muscle strength in both lower extremities. Laboratory findings revealed moderate anemia (hemoglobin 66 g/L), leukopenia (2.70 × 10 9 /L), neutropenia (1.28 × 10 9 /L), hypophosphatemia (0.36 mmol/L), high alkaline phosphatase activity (308.00 U/L), and normal serum calcium (2.22 mmol/L). After surgery, additional examinations were performed to explore the cause of hypophosphatemic osteomalacia. After definitive diagnosis, the patient underwent tumor resection via T11 laminectomy on August 6, 2022. Six months after the second THA, the patient regained normal gait with satisfactory hip movement function without recurrence of PMT-associated osteomalacia or prosthesis loosening. By providing detailed clinical data and a diagnostic and treatment approach, we aimed to improve the clinical understanding of femoral neck fractures caused by TIO.